Some Characteristics of Islamic Law (Prilozi za orijentalnu filologiju, 2017)
Some characteristics of Islamic law in considering and evaluating the role of Islam and that of its legal and social norms, one often comes across a whole series of prejudices, blunders, and unscholarly opinions about Islamic law. Islamic institutions are commonly viewed from the angle of modern. conceptions which bear the marks of Western culture and philosophy. ln this way it is easy to forget the contribution of Islam: to this very culture and philosophy, its role in world history and. its true historical significance for the peoples belonging to its cultural sphere. We must no doubt look on Islamic law with the eyes of modern lawyers, but in doing so we must not by any means, for the sake of scholarly objectivity, losee from sight the historical context of the origin and development of Islamic law as well as its historical role in the life of those nations which were governed by its norms. Starting with these methodological principles, theatricals deals with three clusters of problems: 1) the concept of Islamic law; 2) the origins of Islamic law; and 3) the schools in Islamic law. An analysis of these problems shows that Islamic law represents an original system the historical and moral value of which cannot be judged outside the conditions of its rise and development.